Synthesis, Characterization and Immunological Evaluation of Self‐Adjuvanting Group A Streptococcal Vaccine Candidates Bearing Various Lipidic Adjuvanting Moieties. (15th February 2017) - Fagan, Vincent; Hussein, Waleed M.; Su, Mei; Giddam, Ashwini K.; Batzloff, Michael R.; Good, Michael F.; Toth, Istvan; Simerska, Pavla
Abstract: Four group A streptococcal glycolipopeptide vaccine candidates with different lipidic adjuvanting moieties were prepared and characterized. The immunogenicity of the compounds was evaluated by macrophage and dendritic cell uptake studies and by in vivo quantification of systemic IgG antibody by ELISA. Three of the candidates showed significant induction of the IgG response. Abstract : Adjuvanting antigens : Four group‐A streptococcal glycolipopeptide vaccine candidates possessing B‐ (blue) and T‐cell (green) epitopes and different lipidic adjuvanting moieties (red) were synthesized, characterized, and evaluated in mice. Three of the vaccine candidates showed significant induction of IgGs.